Understanding Things Fall Apart a Student Casebook to Issues, Sources, and Historical Documents - Ogbaa, Kalu (Greenwood Press "Literature in context" series, 1999)
Things Fall Apart is the most widely read and influential African novel. Published in 1958, it has sold more than eight million copies and been translated into fifty languages. African culture is not familiar to most American readers however, and this casebook provides a wealth of commentary and original materials that place the novel in its historical, social, and cultural contexts. Ogbaa, an Igbo scholar, has selected a wide variety of historical and firsthand accounts of Igbo history and cultural heritage. These accounts illuminate the historical context and issues relating to the c
Keywords: Achebe, Chinua. Things fall apart; Civilization; Sources; Igbo (African people) in literature; Igbo (African people); Nigeria; dept.eng; faculty_collection